Curplast - A new generation green additive for plastic - Nurafifah, Othman; Nik Noriman, Zulkepli, Dr.; Sharifah Shahnaz, Syed Bakar, Dr.; Muhammad Salihin, Zakaria; Ahmad Azrem, Azmi; Lokman Hakim, Ibrahim; Mohd Saiful Nizwan, Mhd Salleh (Ministry of Education, Thailand, 2012)
Norafifah Othman and her team won gold medal at 8th International Exhibition for Young Inventors (IEYI 2012), 28th - 30th June 2012 was held at Bangkok International Trade and Exhibition Centre (BITEC), Bangkok, Thailand.